Sulfate-deficient calcium-containing porous mineral materials

JP7642053B2Active Publication Date: 2025-03-07FRAUNHOFER GESELLSCHAFT ZUR FORDERUNG DER ANGEWANDTEN FORSCHUNG EV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023501684
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-13
Filing Date
2021-06-30
Publication Date
2025-03-07
Estimated Expiration
2041-06-30

AI Technical Summary

Benefits of technology

【0106】 また、ヒドロゲルが水分バランスの調整器としても機能し、その後のオートクレーブ処理に有益な効果をもたらすことができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642053000003
    Figure 0007642053000003
  • Figure 0007642053000004
    Figure 0007642053000004
  • Figure 0007642053000005
    Figure 0007642053000005
Patent Text Reader

Abstract

The present invention relates to a calcium-containing porous mineral material having a sulfate content of 1.5 wt. % or less and a biopolymer content in the range of 0.001 wt. % to 5.0 wt. % based on the total weight, a process for producing said material using a biopolymer as a stabilizer, and the use of a biopolymer in the production of a low sulfate calcium-containing porous mineral material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a calcium-containing porous mineral material having a sulfate content of less than 1.5% by weight and a biopolymer content in the range of 0.001% to 5.0% by weight, based on the total weight, to a process for producing said material using a biopolymer as a stabiliser and to the use of a biopolymer in the production of a low-sulfate calcium-containing porous mineral material. [Background technology]

[0002] In addition to their wide range of uses, lightweight porous materials in the construction sector are also efficient products that, due to their low density, help conserve resources. However, despite the reduction in mass, it is important to obtain important material parameters (e.g. compressive strength, flexural strength, etc.) and, accordingly, the processes used in their production become highly technological and standardized. In the production of calcium-containing porous building materials such as autoclaved aerated concrete, foamed concrete, foamed cement, lime foam, etc., it is for example the stabilization of the articles and molding compounds after the foaming or porosification treatment, the so-called green body, that is crucial for the quality of the final product and must be controllable accordingly. In general, the more porous the building material to be produced, the more unstable the green body. For material-related reasons, basic formulations can only be adapted to a limited extent, so additives are added accordingly for stabilization or optimization of certain properties.

[0003] However, here, the negative effects of additives must also be taken into account, which have so far mainly been related to ecological aspects. Such negative effects are especially evident in the CO2 emissions generated during the production process or also in the recyclability of these materials. Here, autoclaved aerated concrete can be taken as an example. To these mixtures, cement and / or sources of calcium sulfate such as anhydrite / gypsum / bassanite are added as stabilizers. Although these materials can also serve as sources of calcium and silicates, the stabilizing function of these materials means that they are added mainly as functional additives that are not required for the formation of tobermorite, the main component of autoclaved aerated concrete. Here, it must be taken into account that the sulfate-containing components of substances such as anhydrite / gypsum / bassanite and cement (where the sulfate content of about 5% acts as a reaction modifier) ​​can be easily leached out and can enter the soil or groundwater, so that such substances lead to a high landfill class at the end of the service life of the building material. The impacts of cement use are also relevant during production and are reflected in particular in CO2 equivalents. The aspects mentioned are known and have already been the subject of several studies, but up until now these aspects have been "unimportant" for the product economy. The only relevant societal change is that this perspective has changed significantly and that scientists and manufacturers are being encouraged to present new solutions.

[0004] The existing and most commonly used solutions for stabilizing green bodies are currently based on the following approaches: 1. Additives that affect the "setting behavior" of unfired products or final products Daake, Henning-Felix from (2016): [Options for optimizing the mode of action of construction chemical additives through mechanisms of controlled active substance release]. a. Calcium oxide Tungulin, Dmitry; Behrenberg, Birgit; Lutter, Jurgen; Wallmeier, Werner (2018): Quicklime with defined reaction time window for aerated autoclaved concrete production, ce / papers 2(4), pp. 223-229. b, cement, anhydrite, gypsum (hemihydrate) Baltakys, K.; Siauciunas, R. (2010): Influence of gypsum additive on the gyrolite formation process, Cement and Concrete Research 40(3), pp.376-383. Malecki, Marek; Kurdowski, Wieslaw; Walczak, Pawel (2018): Influence of gypsum and limestone, used as mineral additives, on autoclaved aerated concrete properties, ce / papers 2(4), pp.231-234. c. Ash Walczak,Pawel;Szymanski,Pawel;Rozycka,Agnieszka(2015):Autoclaved Aerated Concrete based on Fly Ash in Density 350 kg / m 3 as an Environmentally Friendly Material for Energy-Efficient Constructions, Procedia Engineering 122,pp.39-46, Winkels, Bernd; Nebel, Holger; Raupach, Michael (2018): Carbonation of autoclaved aerated concrete containing fly ash, ce / papers 2(4), pp. 47-51. d. Alumosilicate Matsushita, Fumiaki; Imasawa, Kouichi; Shibata, Sumio; Horiguchi, Masatoshi (2018): Aluminum silicate recycling raw materials for production of autoclaved aerated concrete, ce / papers 2(4), pp. 215-221, Grabowska, Ewelina (2018): Zeolites as a raw material to the AAC production, ce / papers 2(4), pp.201-206. e. Pozzolan Luke, K. (2004): Phase studies of pozzolanic stabilized calcium silicate hydrates at 180℃, Cement and Concrete Research 34(9), pp.1725-1732. 2. Additives that act as reinforcing materials and strengthen the supporting structure, such as glass fiber, carbon fiber, cellulose fiber, and synthetic polymer fiber Stadie, R., (2008): Strength behavior and deformation behavior of autoclaved aerated concrete reinforced with short fibers, Doctoral Thesis, Berlin: Technical University of Berlin, [Strength behavior and deformation behavior of autoclaved aerated concrete reinforced with short fibers], Laukaitis, A.; Keriene, J.; Mikulskis, D.; Sinica, M.; Sezemanas, G. (2009): Influence of fibrous additives on properties of aerated autoclaved concrete forming mixtures and strength characteristics of products, Construction and Building Materials 23(9), pp.3034 - 3042, Laukaitis, Antanas; Keriene, Jadvyga; Kligys, Modestas; Mikulskis, Donatas; Lekunaite, Lina (2012): Influence of mechanically treated carbon fibre additives on structure formation and properties of autoclaved aerated concrete, Construction and Building Materials 26(1), pp. 362 - 371, Laukaitis, A.; Keriene, J.; Mikulskis, D.; Sinica, M.; Sezemanas, G. (2009a): Influence of fibrous additives on properties of aerated autoclaved concrete forming mixtures and strength characteristics of products, Construction and Building Materials 23(9), pp. 3034-3042, Karlstetter, C., (2013): Verbesserung der Leistungsfahigkeit von Porenbeton durch den Einsatz von Fasern, Dissertation, Munich: University of the German Federal Armed Forces Munich: [Improving the performance of autoclaved aerated concrete through the use of fibers]. 3. Additives that affect the water balance / viscosity and prevent the unsolidified product from falling apart, e.g. polyvinyl alcohol Akthar, FK; Evans, JRG (2010): High porosity(>90%) cementitious foams, Cement and Concrete Research 40(2), pp.352-358. 4. Utilizing different particle size distributions Isu,Norifumi;Teramura,Satoshi;Ishida,Hideki;Mitsuda,Takeshi:Influence of quartz particle size on the chemical and mechanical properties of autoclaved aerated concrete (II) fracture toughness, strength and micropore, Park, Seung Bum; Yoon, Eui Sik; Lee, Burtrand I. (1999): Effects of processing and materials variations on mechanical properties of lightweight cement composites, Cement and Concrete Research 29(2), pp. 193-200. 5. Adjusting the water / solid ratio Wu,Lixian;Peng,Xiaoqin;Yang,Junfeng;Bai,Guang(1996): Influence of some technology parameters on the structures of autoclaved lime-sand concrete, Cement and Concrete Research 26(7), pp.1109-1120.

[0005] The present invention now describes a novel process for the production of said calcium-containing porous mineral materials, which allows the stabilization of the porosity bodies and the partial or complete replacement of cement, additives such as gypsum / anhydrite / bassanite or other additives such as amorphous silica, pozzolans, by the use of biomimetics. This brings unprecedented economic and ecological advantages for such building materials. For example, the absence of cement allows a significant reduction in the CO2 equivalent. Also, the reduction of the sulfate content means that the building material falls into a lower landfill class. Summary of the Invention

[0006] The present invention relates to a calcium-containing porous mineral material having a sulfate content of 1.5 wt % or less and a biopolymer content in the range of 0.001 wt % to 5.00 wt %, based on the total weight.

[0007] The present invention also relates to a process for the production of the calcium-containing porous mineral material described herein, said process comprising the steps of: a) producing an aqueous suspension comprising a source of calcium oxide, optionally one or more further sources of mineral raw materials and one or more biopolymers; b) producing a green body from the suspension of step a); c) hardening the green body from step b); d) obtaining a calcium-containing porous mineral material.

[0008] Finally, the present invention relates to the use of biopolymers in the manufacture of low calcium sulfate content porous mineral materials. [Brief description of the drawings]

[0009] [Figure 1] A schematic diagram of an example of the "egg-box" model related to calcium alginate is shown. (Source: Fu, Shao, Thacker, Ankur, Sperger, Diana M., Boni, Riccardo L., Buckner, Ira S., Velankar, Sachin et al. (2011): Relevance of rheological properties of sodium alginate in solution to calcium alginate gel properties, AAPS PharmSciTech 12(2), pp. 453-460.) [Diagram 2] Scanning electron microscope (SEM) images show the condition of the inner surface of autoclaved aerated concrete with added ammonium alginate (left) or sodium alginate (right). [Diagram 3]FTIR spectra of alginic acid, ammonium alginate and sodium alginate and of extracts of three autoclaved aerated concrete blocks produced in the Examples section using alginic acid (sample 1), ammonium alginate (sample 2) and sodium alginate (sample 3) are shown. At the bottom of the figure, the respective reference spectra (Na alginate, Ca alginate) are overlaid and the relevant peaks are indicated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] definition For the purposes of the present invention, mineral materials are inorganic non-metallic materials composed of natural minerals or shaped mixtures of materials composed of sieved or crushed minerals, where the desired strength is obtained by using binders, optionally with special hardening treatments. For the purposes of the present invention, excluded from the term mineral materials are wood, metal materials, glass, plastics and composite materials made of these materials.

[0011] According to the above definition, a calcium-containing porous mineral material is a mineral material which has at least a detectable content of calcium and in which deliberate pore formation is also detectable.

[0012] Biopolymers are polymers synthesized in the cells of living organisms (natural polymers). For the purposes of the present invention, the term biopolymer also includes biopolymers obtained by modifying organic compounds in the cells of living organisms (for example, by fermentation in bacteria) (biogenic polymers) and derivatives of biopolymers. For the purposes of the present invention, biodegradable petroleum-based polymers are not included in the term biopolymer.

[0013] A low sulfate material has a sulfate content of less than or equal to 1.5% by weight, based on the total weight of the material.

[0014] Sulfate free materials have no measurable sulfate content.

[0015] The present invention relates to a calcium-containing porous mineral material having a sulfate content of 1.5 wt % or less and a biopolymer content in the range of 0.001 wt % to 5.00 wt %, based on the total weight.

[0016] The calcium-containing porous mineral material preferably comprises Autoclaved aerated concrete and Foam concrete / foam cement, Alkali-activated building materials (geopolymers) and Porous refractory materials (refractory ceramics, refractory concretes), i.e. materials used for high-temperature processes (>600°C) or for furnace linings or thermal aggregates; Porous mineral insulation materials for the construction industry based on foam concrete (hydraulic) or aerated concrete (autoclaved), Porous mineral insulation materials for the industrial insulation of pipes, containers, boilers, furnaces and heating cabinets based on foamed concrete (hydraulic) or aerated concrete (autoclaved); Ceramic foam and Lime foam and Porous air-hardening lime, which is carbonated and hardened in air or in a CO2-enriched atmosphere or in liquid CO2; Mineral-based porous sound absorbing materials; Porous granulates for lightweight concrete.

[0017] The calcium-containing porous mineral building material is preferably a compound as described above.

[0018] Specifically, autoclaved aerated concrete, foamed concrete, foamed cement, and lime foam are preferred, with autoclaved aerated concrete being particularly preferred.

[0019] The content of sulfate in the material is 1.5% by weight or less, preferably 1.0% by weight or less, particularly preferably 0.7% by weight or less, based on the total weight of the material.

[0020] In particularly preferred embodiments, the material does not contain any measurable weight percentage of sulfates.

[0021] Thus, the materials of the present invention are low or sulfate free.

[0022] The sulfate content can be detected / determined by X-ray fluorescence analysis of the material or a sample of the material.

[0023] Furthermore, the content of the biopolymer in the above material is preferably in the range of 0.001% by weight to 5.00% by weight, more preferably 0.01% by weight to 2.50% by weight, particularly preferably 0.05% by weight to 1.00% by weight, and most preferably 0.1% by weight to 0.50% by weight, relative to the total weight of the material.

[0024] Once extracted from the material, the biopolymer components can be detected and determined by conventional detection methods such as FTIR, Raman spectroscopy, gas chromatography, etc., as described in the methods section.

[0025] The biopolymer is preferably one that forms a hydrogel and forms crosslinks via divalent ions such as calcium or magnesium ions, preferably calcium ions.

[0026] The biopolymer is preferably heat resistant and / or stable over a wide pH range, preferably in the alkaline range.

[0027] The material may comprise one or more biopolymers. Preferably, the material comprises one biopolymer.

[0028] Preferred biopolymers are polysaccharides such as alginic acid and its derivatives, pectin(s) and its derivatives, poly-L-guluronic acid and its derivatives, poly-D-mannuronic acid and its derivatives, agar-agar, carrageenan, furcellaran, tragacanth, gum arabic, xanthan gum, karaya gum, gellan gum, and mixtures thereof, preferably alginic acid and its derivatives, pectin and its derivatives, and mixtures thereof, and more preferably alginic acid and its derivatives, and mixtures thereof.

[0029] In this context, derivatives are, for example, salts, esters, amides or glycols.

[0030] Preferred alginic acid derivatives are salts of alginic acid such as sodium alginate, potassium alginate, ammonium alginate, calcium alginate, and propylene glycol alginate.

[0031] Preferred pectin derivatives are high ester pectins having a degree of esterification of more than 50%, low ester pectins having a degree of esterification of 5-50%, pectic acid, and amide pectins.

[0032] Particularly preferred biopolymers are alginic acid, sodium alginate, and ammonium alginate, with alginic acid and ammonium alginate being especially preferred.

[0033] The material preferably does not contain detectable contents of plasticizers, surface-active substances such as, for example, naphthalenesulfonates or ligninsulfonates, or dispersing substances such as melamine resins, polycarboxylates or polycarboxylate ethers.

[0034] The materials can be produced in all known dry bulk density classes.

[0035] Therefore, the above materials have a strength of 50 to 1000 kg / m 3 It is preferred that the dry bulk density of the cellulose acylate is 0.05 to 0.15.

[0036] However, the process described below for producing the material according to the invention proves to be most advantageous when producing a material having a low dry bulk density.

[0037] Thus, in a particular embodiment, the material has a strength of 50 to 400 kg / m 3 It is preferred that the dry bulk density of the cellulose acylate is 0.05 to 0.15.

[0038] In particular, for materials such as foam concrete or foam cement, the present invention provides a compressive strength of 120 kg / m 3 or 100kg / m 3 It is possible to achieve lower dry bulk densities of up to 1000 g / m2.

[0039] In a further aspect, the present invention relates to a process for the production of the calcium-containing porous mineral material described herein, said process comprising the steps of: a) producing an aqueous suspension comprising a source of calcium oxide, optionally one or more further sources of mineral raw materials and one or more biopolymers; b) producing a green body from the suspension of step a); c) hardening the green body from step b); d) obtaining a calcium-containing porous mineral material.

[0040] The process according to the invention comprises, for example, the hardening of the green body by autoclave in the production of autoclaved aerated concrete. a) preparing an aqueous suspension comprising a calcium oxide source, a silicate source and one or more biopolymers; b) producing a green body from the suspension of step a); c) autoclaving the green body from step b) in saturated steam at a temperature in the range of 100°C to 200°C; d) obtaining a calcium-containing porous mineral material.

[0041] In a further embodiment of the process according to the invention, the green body can be cured at room temperature in air or at elevated temperatures in a drying cabinet or heated oven. In this case, the process comprises: a) producing an aqueous suspension comprising a source of calcium oxide, optionally further sources of mineral raw materials and one or more biopolymers; b) producing a green body from the suspension of step a); c) curing the green body from step b) at room temperature in air or at elevated temperature in a drying cabinet or heated oven; d) obtaining a calcium-containing porous mineral material.

[0042] In a further embodiment of the process according to the invention, in the production of an exemplary foamed concrete, the protein in the form of a foam prepared as required, the surfactant, the aluminum powder (to adjust the pH of the suspension as required) and further substances used for this purpose are added, for example, to the suspension which is subjected to porosification. The mineral foam thus produced can be poured into a suitable mould. The green body obtained is usually cured in air. A process suitable for this embodiment is described, for example, in DE19632666C1 or DE10314879A1.

[0043] The suspension is preferably prepared according to step a) by mixing the dry compound with water.

[0044] The dry compound comprises a mixture of a calcium oxide source, optionally one or more further sources of mineral raw materials, one or more biopolymers and optionally further additives.

[0045] The calcium oxide source is preferably selected from lime, such as quicklime or slaked lime, or mixtures thereof.

[0046] Preferably, the lime source does not include cement sources such as gypsum / anhydrite / basanite or calcium sulfate sources.

[0047] Depending on the material being produced, the dry compound may contain one or more additional sources of mineral raw materials.

[0048] By way of example, in the production of autoclaved aerated concrete, a silicate source, preferably selected from quartz sand, fly ash and amorphous silicate or mixtures thereof, is usually added to the dry compound as a further source of mineral raw materials.

[0049] The biopolymer is preferably one that forms a hydrogel and forms crosslinks via divalent ions such as calcium or magnesium ions, preferably calcium ions.

[0050] The biopolymer is preferably heat resistant and / or stable over a wide pH range, preferably in the alkaline range.

[0051] Preferred biopolymers are polysaccharides such as alginic acid and its derivatives, pectin and its derivatives, poly-L-guluronic acid and its derivatives, poly-D-mannuronic acid and its derivatives, agar, carrageenan, furcellaran, tragacanth, gum arabic, xanthan gum, karaya gum, gellan gum, and mixtures thereof, preferably alginic acid and its derivatives, pectin and its derivatives, and mixtures thereof, and more preferably alginic acid and its derivatives, and mixtures thereof.

[0052] In this context, derivatives are, for example, salts, esters, amides or glycols.

[0053] Preferred alginic acid derivatives are salts of alginic acid such as sodium alginate, potassium alginate, ammonium alginate, calcium alginate, and propylene glycol alginate.

[0054] Preferred pectin derivatives are high ester pectins having a degree of esterification of more than 50%, low ester pectins having a degree of esterification of 5-50%, pectic acid, and amide pectins.

[0055] Particularly preferred biopolymers are alginic acid, sodium alginate, and ammonium alginate, with alginic acid and ammonium alginate being especially preferred.

[0056] The proportion of calcium oxide source in the dry compound is preferably within the normal range for each material.

[0057] In the case of autoclaved aerated concrete, the proportion of the calcium oxide source in the dry compound is usually 20% by weight to 50% by weight, preferably 25% by weight to 48% by weight, more preferably 28% by weight to 45% by weight, based on the total weight of the dry compound.

[0058] The proportion of possible further raw material sources in the dry compound is preferably within the usual range for each material.

[0059] In the case of autoclaved aerated concrete, the proportion of the silicate source in the dry compound is usually 35% to 60% by weight, preferably 40% to 58% by weight, more preferably 45% to 55% by weight, based on the total weight of the dry compound.

[0060] The proportion of the biopolymer in the dry compound is usually 0.001% by weight to 5.0% by weight, preferably 0.1% by weight to 2.5% by weight, and more preferably 0.2% by weight to 1.0% by weight, based on the total weight of the dry compound.

[0061] Further additives may also be added to the dry compound.

[0062] In the manufacture of materials according to conventional processes in the prior art, binders such as calcium oxide, cement, gypsum / anhydrite / basanite etc. are usually added to the dry compound or suspension to stabilize the green body to some extent.

[0063] In the production of materials by the process of the present invention, the addition of biopolymers means that cement, in particular portland cement, can be completely or partially omitted as a binder. In some embodiments, the use of binders in general can be completely omitted. In some other embodiments, the proportion of binders in general can be significantly reduced.

[0064] Examples of suitable binders in the process of the present invention include cement, CA cement, hydraulic lime, quicklime, clay, loam, resins, waxes, and alkali-activated binder systems.

[0065] It is preferred that the binder have low or no measurable sulfate content.

[0066] The percentage of possible binder in the dry compound is preferably within the normal range for the respective material. In some embodiments, the binder can be used in a lower than normal percentage. In some other embodiments, the binder can be omitted entirely.

[0067] In the case of autoclaved aerated concrete, the proportion of cement-based binder in the dry compound is usually 0% to 20% by weight, preferably 1% to 17% by weight, more preferably 3% to 15% by weight, based on the total weight of the dry compound.

[0068] The dry compound or the suspension may contain pore formers, which are preferably added to the suspension. Examples of pore formers include reactive metal powders, hydrogen peroxide, etc.

[0069] In the manufacture of some materials, instead of pore formers, other porosifying treatments are applied.

[0070] Porosity, either through the addition of pore formers or other porosity treatments, helps to tailor the density of the material.

[0071] The percentage of possible pore formers in the dry compound is preferably within the normal range for the respective material.

[0072] It is particularly preferred that the dry compound contains as low a proportion as possible of sulfate-containing materials such as gypsum, Portland cement, anhydrite or bassanite or mixtures thereof.

[0073] The dry compound preferably contains the sulfate-containing material in a weight percentage of 0 to 10% by weight, more preferably 0 to 8% by weight, and particularly preferably 0 to 5% by weight, based on the total weight of the dry compound.

[0074] In a very particularly preferred embodiment, the dry compound does not contain sulfate-containing materials such as gypsum, Portland cement, anhydrite, hemihydrate or mixtures thereof.

[0075] The drying compound is preferably free of plasticizers, for example selected from surface-active substances such as naphthalenesulfonates or ligninsulfonates, or dispersing substances such as melamine resins, polycarboxylates or polycarboxylate ethers.

[0076] The suspension is prepared from the dry compounds by adding water.

[0077] In step b) a green body is formed from the suspension as described above.

[0078] This step is usually carried out by transferring the suspension into a mold which is preferably coated or wetted with a release agent.

[0079] The suspension typically foams and swells within the mold due to the formation of gas bubbles from a chemical reaction between the pore former and the calcium oxide source.

[0080] In some embodiments, for example in the production of foamed concrete or foamed cement, the suspension is first foamed and then the mineral foam is transferred into a mold.

[0081] In some embodiments, the foamed suspension typically partially solidifies to the extent that it can be cut into blocks, resulting in a green body.

[0082] Here, the partial setting time is preferably within the normal range for each material.

[0083] The green body can be studied for the above components, and the percentages of calcium oxide source, any further raw material sources, biopolymer, and any further additives can be recalculated to the above percentages in the dry compound by subtracting the percentage of water in the green body.

[0084] Preferably, the green body does not contain additives that increase the proportion of sulfates and / or plasticizers in the green body.

[0085] In step c) the green body from step b) is hardened.

[0086] The appropriate treatment for hardening the green body is: -Hydrothermal hardening, autoclave / steam hardening (autoclaved aerated concrete, autoclaved mineral insulation) - Hydraulic setting or "hardening" in air at room temperature (foam concrete, mineral insulation, cement and / or lime based); - Hydraulic setting or "hardening" in ovens at high temperatures (60-200°C) (foam concrete, mineral insulation, cement and / or lime based) - "hardening" and "curing" by microwave excitation (physical and chemical solidification of the alkali-activated binder system (geopolymer)); Thermal curing or "hardening" in kilns at very high temperatures, such as -600°C or higher, sintering (firing) (refractory ceramics, porous refractory concrete, non-porous refractory concrete, ceramic insulation, ceramic foams) and drying the "green body" at moderate temperatures (approximately 120°C) prior to the sintering (firing) process to prevent the "green body" from cracking during the subsequent sintering process; - Setting or "hardening" by carbonation in the presence of CO2 (porous air-hardening lime mortar, lime foam) -setting or "hardening" by carbonation in a CO2 atmosphere (porous air-hardening lime mortar, lime foam); - Setting or "hardening" by carbonation in liquid CO2 in a pressure vessel (porous air-hardening lime mortar, lime foam)

[0087] In one embodiment, the green body is hardened by autoclaving, this embodiment being preferably used in the manufacture of autoclaved aerated concrete according to the invention.

[0088] In this embodiment, the green body from step b) is then autoclaved in a saturated steam atmosphere at high temperatures of 100-250° C. in a next step.

[0089] The autoclave conditions are not specific to this embodiment of the process according to the invention and can be selected from those known in the art according to the materials used and the desired property profile to be achieved for the materials.

[0090] Step c) is usually carried out in an autoclave.

[0091] Steam is typically provided via a steam generator.

[0092] The autoclaving is usually carried out for 2 to 15 hours, preferably 3 to 12 hours.

[0093] During this process the green body hardens, as a result of which a calcium-containing porous mineral material, preferably autoclaved aerated concrete, is formed.

[0094] This is obtained at the end of step c).

[0095] The calcium-containing porous mineral material thus obtained, preferably autoclaved aerated concrete, preferably has all the characteristics and properties described herein.

[0096] In the process according to the invention, the biopolymer added to the suspension has different roles:

[0097] Firstly, the biopolymer ensures the stabilization of the green body, which allows a high degree of porosity and therefore reduces the dry bulk density of the material. The stabilization of the green body can be observed in particular in materials such as foamed concrete, foamed cement, alkali-activated building materials, porous refractory materials, porous mineral insulation for the construction industry based on foamed concrete, porous mineral insulation for industrial insulation based on foamed concrete, foamed ceramics, foamed lime, porous air-hardening lime, porous mineral-based sound-absorbing materials or porous granules for lightweight concrete as mentioned above.

[0098] Another important role of biopolymers is their strength-enhancing function, which allows the proportion of binders, especially cement, especially Portland cement, to be reduced in some materials, which in turn reduces the sulfate content of such materials and also significantly reduces the CO2 equivalent of the final material. This property of biopolymers can be observed in particular in materials such as autoclaved aerated concrete, porous mineral insulation for the construction industry based on autoclaved aerated concrete, porous mineral insulation for industrial insulation based on autoclaved aerated concrete, or porous mineral-based sound absorbers as mentioned above.

[0099] Biopolymers can also regulate the moisture balance during the manufacturing process by positively influencing the water retention capacity of the mixture.

[0100] Biopolymers also help tailor flow and shear properties.

[0101] Overall, biopolymers can replace calcium sulfate, partially or completely mimicking its functionality.

[0102] These tasks are believed to be associated with the properties of the biopolymers used to form crosslinks with divalent ions such as calcium or magnesium ions.

[0103] Here, these ions are complexed with the polymer chains while a structure reminiscent of an egg crate is formed, resulting in the formation / additional stabilization of the hydrogel.

[0104] This structure is shown in Figure 1, using calcium alginate as an example (Source: Fu, Shao, Thacker, Ankur, Sperger, Diana M., Boni, Riccardo L., Buckner, Ira S., Velankar, Sachin et al. (2011): Relevance of rheological properties of sodium alginate in solution to calcium alginate gel properties, AAPS PharmSciTech 12(2), pp.453-460).

[0105] This changes the viscosity and shear properties of the base compound during the mixing process.The system is also affected by the fact that calcium ions are retained in the hydrogel system.

[0106] The hydrogel may also act as a regulator of moisture balance, which may have a beneficial effect on subsequent autoclaving.

[0107] Figure 2 shows the surface structure of autoclaved aerated concrete with sodium alginate (left) and ammonium alginate (right). Both show uniform platelet formation, and the effect seems to be more pronounced when ammonium alginate is added.

[0108] Thus, the biopolymers are able to mimic and take on the role of gypsum / anhydrite / basanite or binders (especially Portland cement).

[0109] Here, the above effect can be achieved even with a low weight percentage of biopolymer in the material according to the invention, so that the small percentage of biopolymer detectable in the finished material is less than 1.00% by weight. This low weight percentage means that the material does not require a cumbersome approval process. However, the biopolymer can also be added in large amounts, which is generally only limited by economic considerations regarding the cost of the raw materials and the additional approval processes required.

[0110] By using biopolymers as stabilizers, it is possible to significantly or even completely reduce the proportion of sulfate-containing materials and plasticizers.

[0111] This brings economic and ecological advantages for such materials: for example, by not using cement, the CO2 equivalent can be significantly reduced. Furthermore, the reduced sulfate content means that the material falls into a lower landfill class and can be recycled more profitably.

[0112] In a further aspect, the present invention relates to the use of a biopolymer in the manufacture of a low calcium sulfate containing porous mineral material.

[0113] The biopolymer and low sulfate calcium containing porous mineral material preferably have all of the characteristics and properties described herein.

[0114] The properties of the biopolymer as a stabilizer preferably depend on the effects described herein. EXAMPLES

[0115] 1.Measurement method a) Density The dry bulk density was determined according to DIN EN 772-13 after drying the cubes in an oven at a temperature of 105±5° C. until constant weight.

[0116] b) Detection of biopolymers in materials Biopolymers were detected in the materials by extraction using solvents and subsequent analysis of the extracts.

[0117] A sample (10 g) of the final product was ground and added to an alcoholic solution (methanol, ethanol, etc.). The amount of solvent is not critical and can be chosen disproportionately, as in this case (1 part solid, 10 parts solvent). The process can also be accelerated by using a shaking table, stirrers, shakers, etc. In this case, the liquid mixture was put out after 2 weeks. The suspended matter still present in the mixture was removed by centrifugation. The solvent was then removed by evaporation. The removal of the solvent was done by transferring the mixture to a Petri dish and gently warming it. The solids remaining at the bottom were then identified by IR spectroscopy (FTIR). However, other analytical methods (Raman, GC / MS, etc.) are also possible.

[0118] c) X-ray fluorescence analysis (XRF) to determine the weight percentage of components in a material For XRF analysis, a sample pellet of the material was first prepared.

[0119] The samples were ground using a planetary ball mill equipped with a tungsten carbide grinding tool. The grinding of the samples was performed by placing 4-6 ml of sample in a grinding jar equipped with five grinding balls and grinding at 300 rpm for 3 min. The ground sample was passed through an analytical sieve with a mesh size of 50 μm. The residue on the sieve was ground again at 300 rpm for 3 min. This process was repeated until the grain size of the entire sample was less than 50 μm. Due to multiple grinding operations, it was necessary to homogenize the entire sample by placing the entire sample in a sample jar and vibrating for 1 min. The use of other types of mills, grinding media and grinding parameters is also conceivable.

[0120] To produce the pellets, 5 g of the pre-ground sample was mixed with 1.25 g of binder, usually wax, in a sample bottle by adding 3 small steel balls to the sample bottle and vibrating for 1 min. The homogenized sample-binder mixture was introduced into the prepared pressing tool through a 50 μm sieve and pressed for 1 min with a pressure of 25 t. After 1 min, the pressure was gradually released. Care was taken to avoid any sudden leakage of air, as this could result in the formation of cracks in the tablet. For the finished pellets, The uniformity of the surface and Surface homogeneity (the aim is for there to be no visible separation between the binder and the sample) and The inspection and evaluation were carried out in accordance with the standards.

[0121] For XRF analysis, an X-ray spectrometer equipped with a helium flow was used. The finished pellet was introduced into the ready-to-use X-ray spectrometer and moved to the measurement position. When measuring samples of unknown composition, a qualitative analysis must be performed first to identify possible overlaps of the lines. A reference sample must be measured under the same conditions.

[0122] The measurement data were published and evaluated with appropriate software.

[0123] 2. Preparation of Suspension Suspensions were prepared with the dry compounds of Table 1 and water, with a water to dry compound ratio of 0.7.

[0124] [Table 1]

[0125] The biopolymers used were in each case alginic acid (sample 1), ammonium alginate (sample 2) and sodium alginate (sample 3) in the above mentioned proportions. Three different suspensions containing different biopolymers were thus prepared.

[0126] 3. Production of autoclaved aerated concrete The three suspensions were poured into moulds. After expansion treatment, the partially set green bodies were autoclaved in an autoclave under the following conditions: Duration: 6 hours, Pressure: 12-13 bar absolute (saturated steam), ·Temperature: Approximately 180~195℃.

[0127] The mineral material thus obtained (autoclaved aerated concrete) has the chemical composition as shown in Table 2 below. The weight proportions of the various components in the autoclaved aerated concrete were determined by X-ray fluorescence analysis.

[0128] [Table 2]

[0129] The autoclaved aerated concrete material samples 1 to 3 were further investigated for the content of alginic acid or alginates by FTIR according to measurement method b) described above. In the FTIR spectrum in Figure 3, peaks that can be assigned to alginic acid or its salts are identifiable. Thus, the addition of biopolymers in the final product can be detected.

Claims

1. A calcium-containing porous mineral material having a sulfate content of 1.5% by weight or less and a biopolymer content in the range of 0.001% by weight to 5.00% by weight based on the total weight, said biopolymer being a biopolymer that forms a hydrogel and forms crosslinks via divalent ions selected from calcium and magnesium ions.

2. 10. The material of claim 1, which is free of detectable amounts of plasticizers.

3. 3. The material according to claim 1 or 2, wherein the biopolymer is selected from polysaccharides, pectin and its derivatives, poly-L-guluronic acid and its derivatives, poly-D-mannuronic acid and its derivatives, agar, carrageenan, furcellaran, tragacanth, gum arabic, xanthan gum, karaya gum, gellan gum, and mixtures thereof.

4. 50kg / m 3 ~1000kg / m 3 The material according to any one of claims 1 to 3, having a dry bulk density of

5. Autoclaved aerated concrete; Foam concrete / foam cement, - Alkali-activated building materials (geopolymers) and Porous refractory materials (refractory ceramics, refractory concrete), i.e. materials used for high-temperature processes (>600°C) or for furnace linings or thermal aggregates, - porous mineral insulation materials for the construction industry based on foam concrete (hydraulic) or aerated concrete (autoclaved), - porous mineral insulation materials for industrial insulation of pipes, containers, boilers, furnaces, heating cabinets based on foam concrete (hydraulic) or aerated concrete (autoclaved); ・Ceramic foam, - lime foam; Air or CO 2 Enriched atmosphere or liquid CO 2 and porous aerated lime that has hardened by carbonate in the soil. - Mineral-based porous sound-absorbing material; - porous granules for lightweight concrete.

6. A process for producing a calcium-containing porous mineral material according to any one of claims 1 to 5, comprising the steps of: a) preparing an aqueous suspension from dry compounds comprising a calcium oxide source and one or more biopolymers; b) producing a green body from the suspension of step a); c) hardening the green body from step b); d) obtaining a calcium-containing porous mineral material.

7. 7. The process of claim 6, wherein the biopolymer is selected from polysaccharides, pectin and its derivatives, poly-L-guluronic acid and its derivatives, poly-D-mannuronic acid and its derivatives, agar, carrageenan, furcellaran, tragacanth, gum arabic, xanthan gum, karaya gum, gellan gum, and mixtures thereof.

8. 8. The process according to claim 6 or 7, wherein the weight percentage of biopolymer in the dry compound in the suspension ranges from 0.001% to 5.0% by weight relative to the total weight of the dry compound.

9. 9. The process according to any one of claims 6 to 8, wherein the dry compound of the suspension comprises a sulfate-containing material in a weight percentage between 0% and 10% by weight relative to the total weight of the dry compound.

10. 10. The process of claim 9, wherein the sulfate-containing material is selected from gypsum, anhydrite, bassanite, portland cement, and mixtures thereof.

11. The process according to any one of claims 6 to 10, wherein the dry compounds of the suspension are free of plasticizers.

12. 1. Use of a biopolymer for producing a low sulfate calcium containing porous mineral material, said biopolymer being a biopolymer that forms a hydrogel and forms crosslinks via divalent ions selected from calcium and magnesium ions.

Citation Information

Patent Citations

  • Foamed cement composition

    JP2011042551A

  • A method for producing aerated concrete and foamed concrete, and a system for carrying out the said method.

    JP2011516379A

  • Thixotropic water-hardening bonding material

    JP2014062014A

  • Process for preparation of geopolymer foam compositions

    WO2020037349A1